Simulation of α and β gross activity measurement of soil samples with proportional counters. (June 2018) - Alharbi, T.
Abstract: In this paper, we have simulated the performance of a proportional counter for α and β measurement of soil samples. The simulations were performed for α particles from 210 Po and β particles from 90 Sr. The results of the simulations indicate that the maximum count-to-background ratio can be achieved by using sample thicknesses greater than 4 µm and 100 µm, respectively, for α and β measurements. The maximum efficiencies for α and β counting were calculated to be, respectively, 25% and 42.50%. The maximum α-to-β cross talk was also calculated to be 5.51%. The results of the simulations are also compared with the reported experimental values and a good agreement with the experimental results is found. Highlights: A Monte Carlo simulation of proportional counter for α and β measurement of soil samples is presented. The optimum thicknesses of samples for α and β measurements were determined. The maximum efficiencies for α and β counting were calculated to be, respectively, 25% and 42.50%. The maximum α-to-β cross talk was also calculated to be 5.51%.